2020
DOI: 10.48550/arxiv.2008.04836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A polynomial invariant for veering triangulations

Michael Landry,
Yair N. Minsky,
Samuel J. Taylor

Abstract: We introduce a polynomial invariant Vτ P ZrH1pM q{torsions associated to a veering triangulation τ of a 3-manifold M . In the special case where the triangulation is layered, i.e. comes from a fibration, Vτ recovers the Teichmüller polynomial of the fibered faces canonically associated to τ . Via Dehn filling, this gives a combinatorial description of the Teichmüller polynomial for any hyperbolic fibered 3-manifold.For a general veering triangulation τ , we show that the surfaces carried by τ determine a cone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…The connection between veering triangulations and pseudo-Anosov flows inspires a novel direction of research: studying pseudo-Anosov flows via veering triangulations. This idea is exploited by Landry, Minsky and Taylor in [10,11]. In [11] they introduced two polynomial invariants of veering triangulations -the taut polynomial and the veering polynomial.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The connection between veering triangulations and pseudo-Anosov flows inspires a novel direction of research: studying pseudo-Anosov flows via veering triangulations. This idea is exploited by Landry, Minsky and Taylor in [10,11]. In [11] they introduced two polynomial invariants of veering triangulations -the taut polynomial and the veering polynomial.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is exploited by Landry, Minsky and Taylor in [10,11]. In [11] they introduced two polynomial invariants of veering triangulations -the taut polynomial and the veering polynomial. In [10] they showed that these polynomials carry information about the exponential growth rate of the closed orbits of the associated pseudo-Anosov flows [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper relies heavily on the work of Landry, Minsky and Taylor [18]. They defined the taut polynomial, the veering polynomial and the flow graph of a (transverse taut) veering triangulation.…”
Section: Introductionmentioning
confidence: 99%